INDONESIAN DIPLOMACY OF SOUTH-SOUTH COOPERATION TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS 2030 - Leonard Hutabarat (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2022)
South-South Cooperation has played an important role in encouraging development in various countries through strategic programs, such as training, sending experts, providing grants, scholarships, infrastructure, as well as empowering women. Indonesia as one of the countries that plays an active role as a donor country is expected to increase its role in strengthening Indonesia's position as a new emerging donor so that it can improve Indonesia's image in international forums. Diplomacy carried out by Indonesia is part of a constructivism approach in the study of international relations related to the formation of perceptions and values that Indonesia will share with its cooperation partners. South-South Cooperation is not only part of Indonesia's national priority in The National Medium-Term Development Plan 2020-2024, but also provides benefits as a bridge between the needs of beneficiaries and Indonesia's interests, improves Indonesia's positive image in the region and globally, and is part of Indonesia's economic diplomacy. In the recovery after the COVID-19 pandemic, South-South Cooperation is expected to be a part of development cooperation form that can be one of the instruments for restoring conditions and building back better in achieving the goals of Sustainable Development Goals 2030. Keywords: Diplomacy, Indonesia, South-South Cooperation, Sustainable Development Goals 2030